The Neurotoxic Tau45-230 Fragment Accumulates in Upper and Lower Motor Neurons in Amyotrophic Lateral Sclerosis Subjects - Claudia R Vintilescu; Sana Afreen; Ashlee E Rubino; Adriana Ferreira (BMC, 2016)
Abstract Amyotrophic lateral sclerosis (ALS) is a progressive and lethal neurodegenerative disease characterized by loss of upper and lower motor neurons leading to muscle paralysis in affected individuals. Numerous mechanisms have been implicated in the death of these neurons. However, the pathobiology of this disease has not been completely elucidated. In the present study, we investigated to what extent tau cleavage and generation of the neurotoxic tau45-230 fragment is associated with ALS. Quantitative western blot analysis indicated that high levels of tau45-230 accumulated in lumbar and cervical spinal cord specimens obtained from ALS subjects. This neurotoxic tau fragment was also detected in ALS upper motor neurons located in the precentral gyrus. Our results also showed that tau45-230 aggregates were present in the spinal cord of ALS patients. On the other hand, this neurotoxic fragment was not generated in a mouse model of a familial form of this disease. Together, these results suggest a potential role for this neurotoxic tau fragment in the mechanisms leading to the degeneration of motor neurons in the context of sporadic ALS.